DAMPAK PASCA PENAMBANGAN INTAN TERHADAP KUALITAS TANAH DAN AIR DI KELURAHAN PALAM,KECAMATAN CEMPAKA KOTA BANJARBARU KALIMANTAN SELATAN - Eko Rini Indrayatie (Lambung Mangkurat University-Indonesia, 2011)
Diamond mining in Palam Village District Cempaka is one of the people’s. The number of people mine will be positively correlated with the waste that system of diamond mining in Palam Village produce that use the system of dumping. Piles of minerals and mined land will also reduce the physical and chemical properties of soil such as bulk density, pH, CEC and C organic. Water pollution both on the water surface and ground water can occur because Lindian water (leachate) from the waste piles and puddles of water inside the pit. Questions to be answered in this study is how the soil and water quality impacts on post-mining land and which is not mined land. The research was conducted in the land post-mining diamonds in Palam Village District Cempaka Banjarbaru City of South Kalimantan. This land is no longer used for mining since 5 years ago. Soil sampling in the field conducted at two locations, there are the location that have not done as the diamond mining andafter diamond mining land. Replications of samples at each location as many as 3 samples done by purposive sampling. The results demonstrate the physical and chemical soil quality in the study area that includes Bulk Densityand structure of the soil that showing no difference between the lnot mined land with post-mining land, while the chemical properties of post-mining land is smaller for the parameters CEC (6.96%), C- organic (0.55%) and organic matter (0.95%) than land which is not mined the CEC (11.86%), C-organic (1.24%) and organic matter (2.1%) while for otherwise the soil pH. As for water quality in the two land in the study area are also still within tolerable limits of water quality standards are allowed except for BOD5 parameter which is slightly above the quality standard according to Regulation No. 05 the Governor of South Kalimantan in 2007 and still considered the water quality is not polluted until polluted light.Keywords: diamond post-mining land, chemical and physical properties of soil, water quality